Bilabial Palatalisation in Zulu: A morphologically conditioned phenomenon - van der Spuy, Andrew (Stellenbosch Papers in Linguistics Plus)
This article looks at the question of whether the palatalisation processes which occur in the Zulu locative, diminutive and passive are best regarded as morphologically conditioned or as phonologically conditioned. For each of these processes, arguments are presented to show that they are morphologically conditioned, and that proposed analyses of them as phonologically conditioned are incorrect. It is further argued that the rules which prevent VV sequences from arising are also morphologically conditioned. Formal morphologically conditioned analyses of each process are given.